2019
DOI: 10.1038/s41416-019-0589-0
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid X receptor gamma (RXRG) is an independent prognostic biomarker in ER-positive invasive breast cancer

Abstract: Background Retinoid X Receptor Gamma (RXRG) is a member of the nuclear receptor superfamily and plays a role in tumour suppression. This study aims to explore the prognostic significance of RXRG in breast cancer. Methods Primary breast cancer tissue microarrays (n = 923) were immuno-stained for RXRG protein and correlated with clinicopathological features, and patient outcome. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…No studies have so far examined the prognostic value of the intracellular expression of RXRα in BC subcohorts. Previously, Joseph et al reported that high-nuclear retinoid X receptor gamma (RXRG) expression in ER-positive BC tissue samples was associated with a better prognostic impact [69]. This is consistent with previous reports indicating a positive prognostic value of nuclear RXRG in ER-and PR-positive BC [70].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…No studies have so far examined the prognostic value of the intracellular expression of RXRα in BC subcohorts. Previously, Joseph et al reported that high-nuclear retinoid X receptor gamma (RXRG) expression in ER-positive BC tissue samples was associated with a better prognostic impact [69]. This is consistent with previous reports indicating a positive prognostic value of nuclear RXRG in ER-and PR-positive BC [70].…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, both the activation of RXR and the higher expression of RXR in epithelial ovarian cancer have been found to foster pro-apoptotic mechanisms [72]. In BC cells and other tumor entities, RXR is able to execute responses such as cell proliferation, cellular differentiation and programmed cell death [45,69]. Consequently, RXR is a potential therapeutic target in breast cancer cell lines [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear receptor RXR has been proven to modulate cellular differentiation and apoptosis in different tumor entities [ 49 ]. RXR and its heterodimers regulate the function of myeloid cells, link cellular metabolism, and show a profound effect on immune function [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also reported that RXRα was bound by berberine to suppressed β‐catenin in colon cancer 29 30 although the other two isoforms of RXR, β and γ, also have some anti‐tumour effects 31‐36 . However, studies have shown that deficiencies in the α subtype have been shown to have a more detrimental impact on health compared with the other isoforms 37‐39 .…”
Section: Discussionmentioning
confidence: 99%